PEMENUHAN HAK ASASI MANUSIA ATAS BANGUNAN DENGAN KONTRAK BUILT, OPERATE AND TRANSFER - Sarah Selfina Kuahaty (SASI, 2016)
One of the goals of the state as mandated by the Constitution NRI Year 1945 is to promote the general welfare. As mandated by the constitution, the government is obliged to meet the objectives of the country. In addition Article 28 paragraph 1 of the Constitution NRI 1945 also gives the right to every person to live in physical and spiritual prosperity, as a human right. One form of the welfare of society is the availability of infrastructure and facilities to support each activity. The realization of infrastructure facilities such example is building. On one hand the government does not have the funds to provide the building, but the government owns the land. Therefore, the government can invite investors and cooperation for the procurement of the building by using the System Build, Operate and Transfer.